2017
DOI: 10.3390/ijerph14121509
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Emissions, Environmental Policy, and Marginal Abatement Costs

Abstract: Pollution emissions impose serious social negative externalities, especially in terms of public health. To reduce pollution emissions cost-effectively, the marginal abatement costs (MACs) of pollution emissions must be determined. Since the industrial sectors are the essential pillars of China’s economic growth, as well as leading energy consumers and sulfur dioxide (SO2) emitters, estimating MACs of SO2 emissions at the industrial level can provide valuable information for all abatement efforts. This paper tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Li et al [28] used advanced production processes to control urban population growth and proposed an emissions trading system to reduce the economic losses caused by the public health effects of air pollution. He and Ou [29] claimed that it was necessary to determine the marginal pollution emissions abatement costs by first quantifying the sulfur dioxide emissions and then estimate the sulfur dioxide emissions using shadow price theory. They found that China's pollution emissions trading system needed to cover six sectors, including coal mining and coal washing, at the national level.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [28] used advanced production processes to control urban population growth and proposed an emissions trading system to reduce the economic losses caused by the public health effects of air pollution. He and Ou [29] claimed that it was necessary to determine the marginal pollution emissions abatement costs by first quantifying the sulfur dioxide emissions and then estimate the sulfur dioxide emissions using shadow price theory. They found that China's pollution emissions trading system needed to cover six sectors, including coal mining and coal washing, at the national level.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Past studies have focused on the relationship between economic growth and air pollution [4,5], the childhood and elderly diseases caused by excessive air pollution [6][7][8][9][10], the effects of exposure to air pollutants on human health [11][12][13][14][15][16][17][18][19][20][21][22][23][24], and protection measures against the effects of air pollution [25][26][27][28][29][30][31]. Other studies have examined the effectiveness of media campaigns in raising societal awareness of environmental issues [32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…They apply various methods to estimate the economic burden of air pollution, such as the computable general equilibrium model (CGE) to capture the key features of related sectors and markets, as well as the effects of economic activities 20 , the flexible functional forms in demand system analyses to study energy demand or fuel demand (e.g. the Rotterdam model, the Almost Ideal Demand System (AIDS), and the quadratic AIDS (QUAIDS) model) 3,14,21 , the Long range Energy Alternatives Planning System (LEAP) model to track energy consumption, production and resource extraction in all sectors of an economy and consideration of both demand and supply side technologies 22 , and the input-output (I-O) method to distinguish the sectoral emissions and identify the shares of individual industries 10 . This paper focuses on the studies that applied the Impact-Pathway-Approach (IPA) to estimate health impacts and costs caused by air pollution emissions of fossil electricity generation in developing countries.…”
Section: Modelling Of Externalities In Electricity Generationmentioning
confidence: 99%
“…Air pollution is a typical example of negative externalities in economics. Pollution emissions impose serious social negative externalities, especially in terms of public health 10 . Pollutants cause significant damage to both mortality and morbidity (such as bronchitis, respiratory hospital admissions, emergency room visits, asthma, and restricted activity days) due to long or short-term exposure [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the Chinese government has enforced strict regulations to deal with pollutions in the manufacturing industry [ 1 ]. The regulatory pressure urges relevant companies to pay more attention to sustainability aspects of their operational systems with an aim of reducing pollutant emissions.…”
Section: Introductionmentioning
confidence: 99%